The overall regulatory network and contributions of ABC(D)E model genes in yellowhorn flower development - Hanhui Wang; Yanan Lu; Yanru Zhang; Guan Liu; Song Yu; Zhimin Zheng (BMC Plant Biology)
Abstract Background Single flowers and double flowers, exhibiting distinct flower morphologies, developmental process and regulatory networks, have garnered significant attention recently. In yellowhorn (Xanthoceras sorbifolium), the cause of double flower variation has been elucidated, yet the differences in regulatory networks between single and double flowers remain unexplored. Result Here, we investigated transcriptional changes underlying flower development among yellowhorn single- and double-flowered-trees. Transcriptome analysis and weighted gene co-expression network analysis (WGCNA) were applied to identify key genes and reveal the characteristics of single and double flower traits. The involvement of development-specific and flower-type-specific DEGs related to hormone signaling, metabolism, growth and development was identified, and ABC(D)E model genes were found to be closely associated with floral organ development. Overexpression of yellowhorn ABC(D)E model genes in Arabidopsis demonstrated their roles in floral organ development, and the interactions between different pairs of genes were also validated by yeast two-hybrid (Y2H) experiments. Conclusion Therefore we elucidated differences between yellowhorn single and double flower development, highlighting the roles of yellowhorn ABC(D)E model genes in controlling flower structures, which not only enriches the understanding of yellowhorn flower researches, but also provides insights for studying flower development in other woody species.